Reformasi Administrasi Pelayanan Publik pada Kantor Pelayanan Terpadu ( Studi pada Disperindag dan Dispendukcapil Kota Malang ) - Dian Puspitasari (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
Abstrak: The Reform of Public Services Administration at The Office of Integrated Service (studies on the reform of public service administration in the Department of Industry and Trade, and the Department of Civil Registration Malang city). Every citizen requires public services efficiently and effectively to complaints and responsive citizens. In Indonesian public service is still an issue that is still ongoing improvements. So to improve public services necessary administrative reform public services. Office of integrated services reform public services. Location research in the reform of public service administration in the Department of Industry and Trade, and the Department of Civil Registration. The purpose of this research study to describe and analyze the shape of the administrative reform of public services that occurred on the reform of public service administration in the Department of Industry and Trade, and the Department of Civil Registration. Methods this study uses descriptive qualitative research method. The results showed that the reform carried out by streamlining its organizational structure, reform strategies using core strategy and customers, the reform still have some barriers caused by the lack of most human resources who have quality and quantity, and the low participation of the community. Keywords : reformation, administration, public serviceAbstrak: REFORMASI ADMINISTRASI PELAYANAN PUBLIK PADA KANTOR PELAYANAN TERPADU (Studi Pada Disperindag dan Dispendukcapil Kota Malang). Setiap warga Negara memerlukan pelayanan publik yang efisien dan efektif serta responsif terhadap keluhan warganya. Di Indonesia pelayanan publik masih menjadi permasalahan yang sampai saat ini masih terus dilakukan perbaikan. Memperbaiki pelayanan publik diperlukan reformasi administrasi pelayanan publik. Kantor Pelayanan Terpadu Kota Malang untuk meningkatkan pelayanan diperlukan reformasi pelayanan publik. Lokasi penelitian pada Disperindag dan Dispendukcapil Kota Malang. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis bentuk reformasi administrasi pelayanan publik yang terjadi pada Disperindag dan Dispendukcapil Kantor Pelayanan Terpadu Kota Malang. Metode penelitian ini menggunakan metode penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa reformasi dilakukan dengan merampingkan struktur organisasinya, strategi reformasi menggunakan strategi inti dan pelanggan, reformasi masih memiliki beberapa hambatan disebabkan paling banyak oleh kurangnya sumber daya manusia yang memiliki kualitas dan kuantitas, dan rendahnya partisipasi dari masyarakat. Kata kunci: Reformasi, Administrasi, Pelayanan Publik